Macedonian livestock, dairy and grain sectors and the EU accession impact - Ana KOTEVSKA; Dragi DIMITRIVESKI; Emil ERJAVEC (Agricultural Economics (AGRICECON), 2013)
The Republic of Macedonia is in the process of integrating into the European Union (EU) and adjusting its policies through reforms in policy, regulations and institutions. This paper attempts to provide an answer to the question: what would be the impact on the Macedonian livestock, dairy and grain sectors of Macedonia integrating into the EU. In order to forecast the impact of the EU accession, the research uses the partial equilibrium model as a comprehensive tool for modelling the complex nature of the agricultural markets. The model simulation foresees the changes of the modelled sub-sectors in production, net-trade and income. The baseline scenario predicts a positive development for almost all selected commodities, with the exception of the beef sector, which is highly uncompetitive prior to the accession. Three EU accession scenarios foresee positive developments in the beef, lamb and cow's milk markets, while a negative development is expected in the pig meat and grains markets.